2017
DOI: 10.1111/1750-3841.13837
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of Wheat Bread with Agroindustry By‐Products: Statistical Methods for Sensory Preference Evaluation and Correlation with Color and Crumb Structure

Abstract: The use of agroindustry by-products (BP) for fortification of wheat bread can be an alternative to waste disposal because BP are appealing sources of dietary fiber. Moreover, it may also contribute to indirect income generation. In this study, sensory, color, and crumb structure properties of breads fortified with fiber rich fraction recovered from four types of agroindustry BP were tested, namely orange (OE), pomegranate (PE), elderberry (EE), and spent yeast (YE). Statistical models for sensory preference ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The color of bread depends on the formulation or baking condition. Maillard reactions and caramelization of the crust are responsible for the changes in the color parameters between the crust and the crumb and the development of brown color on the surface at high temperature, but the color given to the ingredients used in bread formulation may mask this color [5,55,83,84].…”
Section: Crust and Crumb Color Of Breadmentioning
confidence: 99%
“…The color of bread depends on the formulation or baking condition. Maillard reactions and caramelization of the crust are responsible for the changes in the color parameters between the crust and the crumb and the development of brown color on the surface at high temperature, but the color given to the ingredients used in bread formulation may mask this color [5,55,83,84].…”
Section: Crust and Crumb Color Of Breadmentioning
confidence: 99%
“…As part of an effort to develop health-promoting flatbreads with low acrylamide content, we previously reported that flatbreads made using flours from ancient grains such as brown rice, buckwheat, cornmeal, millet, oats, and quinoa had a lower acrylamide content than flatbreads prepared from potato and wheat flours [8]. We are also engaged in a parallel effort designed to define the potential health benefits of antioxidative fruits and vegetable peels, as well the peel (hull) from rice, which are often discarded as a food-processing waste product [9,10,11]. As part of this effort, we have shown that (a) the dietary supplementation of potato peel powders reduced weight gain in mice on a high-fat diet [12]; (b) potato peel powders inhibited the growth of pathogenic trichomonads (protozoa) that cause sexually transmitted diseases in humans and cattle [13]; (c) apple, orange, and potato peel powders inhibited the outgrowth of pathogenic Bacillus cereus bacteria from spores in cooked rice [14]; and (d) a rice hull smoke extract reduced weight gain in mice on a high-fat diet [15].…”
Section: Introductionmentioning
confidence: 99%
“…The external preference mapping was created using the FREFMAP method (Martins, Pinho, & Ferreira, ) which employed the sensory attribute coordinates in the two‐dimensional factor space resulting from PCA and average overall preference scores for each group obtained by HCA (Figure ). The resulting preference maps indicated the best fitting model for each group in all studied meat product was vector model.…”
Section: Resultsmentioning
confidence: 99%